2014
DOI: 10.1037/spq0000052
|View full text |Cite|
|
Sign up to set email alerts
|

Empathetic responsiveness, group norms, and prosocial affiliations in bullying roles.

Abstract: In this study, the relationships among gender, empathetic responsiveness, perceived group norms, prosocial affiliations, and bullying roles were examined for 262 fifth- through eighth-grade students (n = 141 males; n = 121 females). According to the Bullying Participant Roles Survey (BPRS), participants were identified as defenders (n = 135; 51.5%), victims (n = 48; 18.3%), bullies (n = 39; 14.9%), and outsiders (n = 26; 9.9%). Results of multinominal logistic regression revealed that empathetic responsiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 57 publications
(96 reference statements)
3
32
0
Order By: Relevance
“…In addition, girls were more likely to interpret events as emergencies than boys. In addition, Nickerson and Mele-Taylor (2014) found that girls who had friends with more prosocial affiliations and friends with more pro-bullying attitudes were more likely to be bullies, victims, and outsiders than defenders. There was a significant interaction between victimization and gender, which indicated girls who reported less victimization were more likely to interpret events as an emergency than girls who reported high levels of past victimization; however, for boys, higher victimization was associated with greater likelihood of interpreting bullying as an emergency.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, girls were more likely to interpret events as emergencies than boys. In addition, Nickerson and Mele-Taylor (2014) found that girls who had friends with more prosocial affiliations and friends with more pro-bullying attitudes were more likely to be bullies, victims, and outsiders than defenders. There was a significant interaction between victimization and gender, which indicated girls who reported less victimization were more likely to interpret events as an emergency than girls who reported high levels of past victimization; however, for boys, higher victimization was associated with greater likelihood of interpreting bullying as an emergency.…”
Section: Discussionmentioning
confidence: 98%
“…It is not uncommon for bullies and victims to belong to the same social network, especially for girls (Crick & Werner, 1998). In addition, Nickerson and Mele-Taylor (2014) found that girls who had friends with more prosocial affiliations and friends with more pro-bullying attitudes were more likely to be bullies, victims, and outsiders than defenders. If a girl is bullied and witnesses bullying within her social network, she may be less likely to interpret this as an emergency.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They found that bullying and empathy were negatively associated for boys but not for (younger) girls when the target was a boy, whereas bullying and empathy were negatively associated for girls but not for boys when the target was a girl. Despite these findings, later studies on bullying involvement using empathy measures that distinguished between boy and girl targets, such as the IECA (Bryant, 1982) and the ERQ (Olweus & Endresen, 1998), combined the empathy scores toward both genders into an overall affective empathy score ignoring the empathy target's gender (Barchia & Bussey, 2011;Cappadocia, Pepler, Cummings, & Craig, 2012;Correia & Dalbert, 2008;Nickerson & Mele-Taylor, 2014;Nickerson, Mele, & Princiotta, 2008;Park, 2013;Raskauskas et al, 2010;Warden & Mackinnon, 2003;Woods, Wolke, Nowicki, & Hall, 2009).…”
Section: Gender Of the Empathy Target And Bullying Involvementmentioning
confidence: 99%
“…Feshbach (1978) describes empathy as encompassing three components: 1) cognitive ability to discriminate affective cues in others, 2) mature cognitive skills involved in assuming the perspective of another person, and 3) emotional responsiveness to the experience of emotions. Research has found that empathy and perspective-taking skills in youth are associated with less bullying perpetration (Espelage, Green, & Polanin, 2012) and greater defender behaviors (Barchia & Bussey, 2011;Nickerson & Mele-Taylor, 2014;Pöyhönen, Juvonen & Salmivalli, 2010;Pozzoli & Gini, 2010;Rigby & Johnson, 2006). Thus, it was hypothesized that students who receive the Second Step condition would report less bullying perpetration and physical aggression.…”
Section: Program Inputs: Classroom Curriculum Content Domains Empathymentioning
confidence: 97%